(untitled) (Journal of the College of Basic Education, 2024)
The function of the theatrical show is completed in addition to its artistic role in the guiding aspect, educating the viewer or spectator of the show, and conveying a meaning, according to its intellectual and aesthetic nature. Functional influence is important and fundamental in theatrical works. With the complexity of life and the many problems that accompany it and cause concern to people, especially the forms of extortion, electronic in particular, with the spread of technologies and means of communication, the ease of access to people’s data and the penetration of their privacy, these electronic crimes constitute a source of inconvenience to those in charge of education because they have misguided effects and negatively reflected on education and academic achievement, and with the development of methods And modern teaching methods and the emergence of remedial teaching methods. Educational theater took a larger area of interest by educators, after which it was a live, direct means of influence and change. The researcher adopted the descriptive approach, and the research community consisted of university students, and the researcher chose a sample of university students. The researcher prepared an open questionnaire and presented it to the professors to find out the reasons and areas of influence for theatrical performances in (electronic extortion) as a crime for which the law is held accountable and may cause serious effects on the target groups, especially university students And in the light of their opinions, the restricted questionnaire was prepared and presented to the students, and he reached results, most notably that theatrical performances have a positive contribution to the diagnosis and treatment of this crime, so the researcher recommends holding artistic competitions and encouraging students to prepare texts and theatrical performances that deal with such electronic crim.